2022
DOI: 10.3390/ijms23158269
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of New Chimeric Analogs of Mastoparan from the Wasp Venom Paravespula lewisii

Abstract: Mastoparan (MP) is an antimicrobial cationic tetradecapeptide with the primary structure INLKALAALAKKIL-NH2. This amphiphilic α-helical peptide was originally isolated from the venom of the wasp Paravespula lewisii. MP shows a variety of biological activities, such as inhibition of the growth of Gram-positive and Gram-negative bacteria, as well as hemolytic activity and activation of mast cell degranulation. Although MP appears to be toxic, studies have shown that its analogs have a potential therapeutic appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Jarosław Ruczy ński et al reported that the α-helical structure of a peptide had a significant impact on its interaction with negatively charged membranes. They also found a strong correlation between the helix content of a peptide and antimicrobial activity [26]. This study demonstrated a correlation between the structure of peptides and their biological activity.…”
Section: Lc/ms-ms Chromatography and Peptide Synthesissupporting
confidence: 61%
“…Jarosław Ruczy ński et al reported that the α-helical structure of a peptide had a significant impact on its interaction with negatively charged membranes. They also found a strong correlation between the helix content of a peptide and antimicrobial activity [26]. This study demonstrated a correlation between the structure of peptides and their biological activity.…”
Section: Lc/ms-ms Chromatography and Peptide Synthesissupporting
confidence: 61%
“…To achieve this, the peptide’s secondary structure is an important feature. Numerous reports state mastoparans depend on an α-helix structure to exert their antimicrobial activity [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Peptides from the mastoparan family and their analogs can interact with membranes, potentially disrupting bacterial membranes and viral envelopes [ 42 , 60 ]. However, evaluating such activity in a host cell/viral envelope scenario can be challenging, as the lipid composition of host cells and viral membranes is often quite similar.…”
Section: Resultsmentioning
confidence: 99%
“…Mastoparan is a 14-amino acid amphiphilic peptide with both hydrophobic and hydrophilic residues that form amphipathic helical structures [ 22 ]. Hydrophobic residues can be embedded into the lipid bilayer of the cell membrane, and hydrophilic residues can form pores on the cell membrane, causing instability of the cell membrane structure and increasing its permeability, thereby leading to cell lysis and inactivation [ 6 , 17 , 23 ].…”
Section: Wasp Venom Components Associated With Aki ( Table ...mentioning
confidence: 99%
“…Mastoparan has various biological activities; for examples, it can activate guanylate cyclase in addition to G proteins and phospholipases, leading to muscle cell and renal tubular cell lysis [ 6 , 25 ]. In pharmacology, mastoparan is also important owing its antibacterial, antiviral, and antitumor effects [ 20 , 22 ]; however, its application is limited due to its strong hemolytic toxicity and cytotoxicity [ 26 ].…”
Section: Wasp Venom Components Associated With Aki ( Table ...mentioning
confidence: 99%